2020
DOI: 10.1101/2020.09.25.313296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LAP2alpha maintains a mobile and low assembly state of A-type lamins in the nuclear interior

Abstract: Lamins form stable filaments at the nuclear periphery in metazoans. Unlike B-type lamins, lamins A and C localize also in the nuclear interior, where they interact with lamin-associated polypeptide 2 alpha (LAP2α). We show that lamin A in the nuclear interior is formed from newly expressed pre-lamin A during processing and from soluble mitotic mature lamins in a LAP2α-independent manner. Binding of LAP2α to lamins A/C in the nuclear interior during interphase inhibits formation of higher order structures of la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 60 publications
6
8
0
Order By: Relevance
“…To examine the distribution of lamin A/C in the absence of hepatocyte LAP2α, we performed immunofluorescence staining of mouse liver tissue. Consistent with prior reports (27, 29), livers of HKO mice showed stronger LMNA staining at the nuclear rim compared to WT, with particularly prominent LMNA staining in HKO mice after 8 weeks of HFD ( Figure 3A ); under chow diet conditions, LMNA staining was similar in WT and HKO mouse livers ( Supplementary Figure 2 ). Immunoblot analysis of whole livers did not show significantly different overall LMNA levels in livers from HFD-fed HKO and WT mice ( Figure 3B ).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…To examine the distribution of lamin A/C in the absence of hepatocyte LAP2α, we performed immunofluorescence staining of mouse liver tissue. Consistent with prior reports (27, 29), livers of HKO mice showed stronger LMNA staining at the nuclear rim compared to WT, with particularly prominent LMNA staining in HKO mice after 8 weeks of HFD ( Figure 3A ); under chow diet conditions, LMNA staining was similar in WT and HKO mouse livers ( Supplementary Figure 2 ). Immunoblot analysis of whole livers did not show significantly different overall LMNA levels in livers from HFD-fed HKO and WT mice ( Figure 3B ).…”
Section: Resultssupporting
confidence: 91%
“…These protein-protein interactions influence several physiological functions, including proliferation and differentiation, as well as chromatin organization and gene expression (43-45). Our data, in agreement with prior reports (27, 29), show that loss of LAP2α enhanced LMNA staining at the nuclear periphery without changing its overall expression level, which was accompanied by pro-steatotic, pro-inflammatory, and pro-fibrotic transcriptional changes that were opposite to those seen in Lmna -KO mice. In particular, whereas male mice lacking lamin A/C in hepatocytes were predisposed to steatohepatitis via a dramatic increase in transcriptional expression of pro-steatotic genes including Cidea, Cidec, Mogat1 , and Cd36 (24), in this study we observed opposite changes in the expression of all of these genes in the absence of LAP2α.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nucleoplasmic lamins have been shown to be assembled and to interact with chromatin. 30 To further examine nucleoplasmic lamins, as well as the potential for force transmission between nuclear lamins and chromatin, we developed an additional nanobody sensor, using a previously developed H2A-H2B nanobody, 31 to measure mechanical tension between histone H2A-H2B and lamin A/C (Lamin-histone-SS) (Fig. 4c).…”
Section: Resultsmentioning
confidence: 99%